National field evaluation of a defined substrate method for the simultaneous enumeration of total coliforms and Escherichia coli from drinking water: comparison with the standard multiple tube fermentation method. - Edberg, S C (1988)
A defined substrate method was developed to simultaneously enumerate total coliforms and Escherichia coli from drinking waters without the need for confirmatory or completed tests. It is a new method based on technology that uses a hydrolyzable substrate as a specific indicator-nutrient for the target microbes. No equipment other than a 35 degrees C incubator and long-wavelength (366-nm) light is necessary. To perform the test, one only has to add water to the powdered ingredients in a tube or flask. If total coliforms are present in the water sample, the solution will change from its normal colorless state (no target microbes present) to yellow. The specific presence of E. coli will cause the same tube to fluoresce under a longwave (366-nm) UV lamp. The test, called Autoanalysis Colilert (AC), was compared with Standard Methods for the Examination of Water and Wastewater 10-tube multiple tube fermentation (MTF) in a national evaluation. Five utilities, representing six U.S. Environmental Protection Agency regions, participated. All water samples came from distribution systems. Split samples from a wide variety of water sources were analyzed for the MPN-versus-MPN comparison. A total of 1,086 tubes were positive by MTF, and 1,279 were positive by AC. There was no statistical difference between MTF and AC. Species identifications from positive tubes confirmed the sensitivity of the AC. A national evaluation of the AC test showed that it: (i) was as sensitive as Standard Methods MTF, (ii) specifically enumerated 1 total coliform per 100 ml, in a maximum of 24 h, (iii) simultaneously enumerated 1 E. coli per 100 ml in the same analysis, (iv) was not subject to false-positive or false-negative results by heterotrophic bacteria, (v) did not require confirmatory tests, (vi) grew injured coliforms, (vii) was easy to inoculate, and (viii) was very easy to interpret.